Haematological parameters in a free-ranging population of Didelphis virginiana from Mexico - Zepeda-Espinosa, Joice Y.; Alonzo-Salomón, Ligia G.; Reyes-Novelo, Enrique A.; Ruiz-Piña, Hugo A. (Austral Journal of Veterinary Sciences, 2019)
The American opossum Didelphis virginiana is the marsupial species with the largest geographic distribution in North America, a very important natural host and key to the maintenance and transmission of many zoonotic pathogenic microorganisms of importance in public health, and one of the wild mammals with the greatest adaptation to the human environment, but despite all that very little is known about some physiological aspects in their free-ranging populations. In the present study, basic haematological parameters of 201 opossums from a synanthropic population of D. virginiana in a rural locality of the state of Yucatan, are first described. The average values of haemoglobin, packed cell volume, red blood cells, and eosinophils were higher in males and adults (except eosinophils) than in females and juveniles, respectively, and juvenile opossums had higher values of lymphocytes, neutrophils, and platelets than males. Non-pregnant females had significantly higher values of mean corpuscular volume, lymphocytes and platelets than pregnant ones, while red blood cell count and segmented neutrophils showed higher values in pregnant females. The establishment of the basic haematological parameters for free-ranging populations of D. virginiana is a very useful reference for both the health monitoring of the populations and further studying the host-parasite relationship of some zoonotic pathogens present in the Yucatan Peninsula.